1965
DOI: 10.1111/j.1600-0609.1965.tb01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Occurrence of k Chains in Isolated Cold Haemagglutinins

Abstract: All of 37 cold haemagglutinins isolated from sera of patients with chronic cold haemagglutinin syndrome were shown to contain k chains only. When data obtained from other investigators are added, it appears that a total of at least 59 isolated cold haemagglutinins have been found to contain only type K γM‐globulin molecules. In analogy with current views on the structure of the γG‐globulin molecule, it is suggested that each active site of the cold haemagglutinin molecules is made up by a close interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Considering the lack of effect of corticosteroids and conventional immunosuppressive agents, 1,6,9 it may be hypothesized that mechanisms related to unspecific immune suppression are not essential. Previous studies of rituximab therapy were based on the presence of a clonal lymphoproliferative B-cell disorder in the bone marrow of most if not all patients with primary CAD, 2,4,9,24 testing the hypothesis that targeting the pathogenic cell clone would provide an efficient therapy. 11,12 We previously found, however, that PR was often achieved even though the median IgM level reduction was modest (only 54%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the lack of effect of corticosteroids and conventional immunosuppressive agents, 1,6,9 it may be hypothesized that mechanisms related to unspecific immune suppression are not essential. Previous studies of rituximab therapy were based on the presence of a clonal lymphoproliferative B-cell disorder in the bone marrow of most if not all patients with primary CAD, 2,4,9,24 testing the hypothesis that targeting the pathogenic cell clone would provide an efficient therapy. 11,12 We previously found, however, that PR was often achieved even though the median IgM level reduction was modest (only 54%).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology, pathogenetic mechanisms and clinical features of chronic cold agglutinin disease (CAD) have been quite extensively elucidated in the literature, [1][2][3][4][5] but therapy remains suboptimal. [6][7][8][9][10] Although most authors emphasize the importance of avoiding cold exposure, a population based study showed that drug therapy had been attempted in more than 70% of the patients, 9 indicating that counseling is insufficient as sole therapeutic measure in a majority.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The CAs are almost invariably of the immunoglobulin (Ig) Mk class and have specificity for the I carbohydrate antigen on the erythrocyte surface. [8][9][10][11] Temperatures below normal central body temperature facilitate binding to the antigen, causing agglutination and complement-dependent hemolysis. 2,9,12 The predominant mechanism of erythrocyte breakdown, known as extravascular hemolysis, is phagocytosis of cells opsonized with complement protein C3b, generated by the classical pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The first monoclonal immunoglobulin ever described was a CA from a patient with CAD (Christenson et al , 1957), and monoclonal immunoglobulin (Ig) Mκ was a recurrent finding in subsequent studies (Harboe et al , 1965). In a larger cohort of 86 patients, we detected monoclonal IgMκ in more than 90%, whereas monoclonal IgG, IgA or λ light chain restriction were rare findings (Berentsen et al , 2006).…”
Section: Clonality As Background For Therapymentioning
confidence: 99%